Brazilian research on extremophiles in the context of astrobiology. Issue 4 (October 2012) - Duarte, Rubens T. D.; Nóbrega, Felipe; Nakayama, Cristina R.; Pellizari, Vivian H.
Abstract Extremophiles are organisms adapted to grow at extreme ranges of environmental variables, such as high or low temperatures, acid or alkaline medium, high salt concentration, high pressures and so forth. Most extremophiles are micro-organisms that belong to the Archaea and Bacteria domains, and are widely spread across the world, which include the polar regions, volcanoes, deserts, deep oceanic sediments, hydrothermal vents, hypersaline lakes, acid and alkaline water bodies, and other extreme environments considered hostile to human life. Despite the tropical climate, Brazil has a wide range of ecosystems which include some permanent or seasonally extreme environments. For example, the Cerrado is a biome with very low soil pH with high Al+3 concentration, the mangroves in the Brazilian coast are anaerobic and saline, Pantanal has thousands of alkaline–saline lakes, the Caatinga arid and hot soils and the deep sea sediments in the Brazilian ocean shelf. These environments harbour extremophilic organisms that, coupled with the high natural biodiversity in Brazil, could be explored for different purposes. However, only a few projects in Brazil intended to study the extremophiles. In the frame of astrobiology, for example, these organisms could provide important models for defining the limits of life and hypothesize about life outside Earth. Brazilian microbiologists have, however, studied the extremophilic micro-organisms inhabiting non-Brazilian environments, such as the Antarctic continent. The experience and previous results obtained from the Brazilian Antarctic Program (PROANTAR) provide important results that are directly related to astrobiology. This article is a brief synopsis of the Brazilian experience in researching extremophiles, indicating the most important results related to astrobiology and some future perspectives in this area.